Development of method for synchronous spark excitation of ultra-wideband antenna array elements - Шостко, Игорь Светославович (Technology audit and production reserves, 2015)
To test the effectiveness of screening facilities and equipment to ensure information security simple compact generators of electromagnetic radiation is needed. For this purpose it is proposed to use spark generators-radiators of powerful ultra-wideband microwave pulses. A new method to synchronize the array of spark generators-radiators is offered. This method allows to simplify the synchronization of the antenna array. The analysis of dependence an array factor on switching time of fuses and voltage distribution on the plates of strip radiators at the time of fuses breakdown is conducted. The results of mathematical modeling parameters of the linear array of spark strip radiators are confirmed by experimental results. During the experiment the effect of coherent addition of pulses generated at the breakdown time of the spark gaps of strip radiators has been observed. As a result generator radiation directivity and power has increased.